KAJIAN PENGALOKASIAN EQUIPMENT PARKING AREA (EPA) DI APRON BANDAR UDARA INTERNASIONAL LOMBOK - Rani Khoirun Nisa; Kardi; Sunarno (Politeknik Penerbangan Indonesia Curug, 2018)
RANI KHOIRUN NISA, THE STUDY OF EQUIPMENT PARKING AREA (EPA) MARKING ALLOCATION IN APRON AT LOMBOK INTERNATIONAL AIRPORT, Final Project Diploma III Airport Operation X, Indonesia Civil Aviation Institute, August 2017. As the increasing of air transport development in Lombok International Airport, many Airlines make a new route to Lombok in order to improve services to the flight operators and service users to provide safety and comfort. Marking available at the airport must be in accordance regulations of Keputusan Direktur Perhubungan Udara No. KP 39 Tahun 2015, to create and maintain the discipline of vehicle traffic to be smooth and conducive. Lombok International Airport has no parking area for Ground Support Equipment (GSE) in apron which causes the placement of GSE disorderly and not in the certain area which is placed in the service road. In some cases, this placement interferes with disrupting the traffic flow of vehicles in apron. By looking at the condition, Equipment Parking Area (EPA) marking is made to place the GSE equipment in apron. To overcome the problems, the writer proposed to make EPA in apron by adding EPA marking in each parking stand. By the existence of EPA, hopefully all GSE parked in EPA provide safety operation of flight in air side area. Also, airside area must be more monitored and the discipline is increasing.